Quality of Care for Comorbid Conditions During the Transition to Survivorship: Differences Between Cancer Survivors and Noncancer Controls - Snyder, Claire F. (American Society of Clinical Oncology, 2013)
PURPOSE: Building on previous research documenting differences in preventive care quality between cancer survivors and noncancer controls, this study examines comorbid condition care. METHODS: Using data from the Surveillance, Epidemiology, and End Results (SEER) –Medicare database, we examined comorbid condition quality of care in patients with locoregional breast, prostate, or colorectal cancer diagnosed in 2004 who were age ≥ 66 years at diagnosis, who had survived ≥ 3 years, and who were enrolled in fee-for-service Medicare. Controls were frequency matched to cases on age, sex, race, and region. Quality of care was assessed from day 366 through day 1,095 postdiagnosis using published indicators of chronic (n = 10) and acute (n = 19) condition care. The proportion of eligible cancer survivors and controls who received recommended care was compared by using Fisher's exact tests. The chronic and acute indicators, respectively, were then combined into single logistic regression models for each cancer type to compare survivors' care receipt to that of controls, adjusting for clinical and sociodemographic variables and controlling for within-patient variation. RESULTS: The sample matched 8,661 cancer survivors to 17,322 controls (mean age, 75 years; 65% male; 85% white). Colorectal cancer survivors were less likely than controls to receive appropriate care on both the chronic (odds ratio [OR], 0.88; 95% CI, 0.81 to 0.95) and acute (OR, 0.72; 95% CI, 0.61 to 0.85) indicators. Prostate cancer survivors were more likely to receive appropriate chronic care (OR, 1.28; 95% CI, 1.19 to 1.38) but less likely to receive quality acute care (OR, 0.75; 95% CI, 0.65 to 0.87). Breast cancer survivors received care equivalent to controls on both the chronic (OR, 1.06; 95% CI, 0.96 to 1.17) and acute (OR, 0.92; 95% CI, 0.76 to 1.13) indicators. CONCLUSION: Because we found differences by cancer type, research exploring factors associated with these differences in care quality is needed.